DaF-Unterricht und besondere Bildungsbedürfnisse - Russo, Eriberto (Kritik. Rivista di letteratura e critica culturale, 2023)
The aim of this paper is to explore the relationship between the teaching of German as a foreign language and the universe of special educational needs, while focusing on its theoretical, political, and methodological implications in Italian school system. The contribution is divided into two main parts: the first part focuses on the conceptual and theoretical framework, while moving between special education needs and foreign language teaching; the second part considers the creation of an inclusive foreign language lesson and proposes an intervention scheme for the creation of an inclusive learning unit, while giving concrete inputs regarding the German language.